factorise 5(3x+y)+6(3x+y)-8

Asked by Kriti Arora | 14th Sep, 2013, 01:31: PM

Expert Answer:

The correct expression should be 5(3x + y)+ 6(3x + y) - 8. It can be factorised as follows:
 
Let (3x + y) = z. Then, the expression becomes:
5z+ 6z - 8
= 5z+ 10z - 4z - 8
= 5z(z + 2) - 4(z + 2)
= (z + 2)(5z - 4)
= (3x + y + 2) [5(3x + y) - 4]
= (3x + y + 2) (15x + 5y - 4)

Answered by  | 14th Sep, 2013, 09:23: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.